2022
DOI: 10.56979/401/2022/80
|View full text |Cite
|
Sign up to set email alerts
|

Cyberattacks Detection in IoMT using Machine Learning Techniques

Abstract: Information and Communication Technology (ICT) has changed the computing paradigm. Various new channels for communication are created through these developments, and the Internet of Things (IoT) is one of them. Internet of Medical Things (IoMT) is a part of IoT in which medical devices are connected through a network. IoMT has resolved many traditional health-related problems and has some security concerns. This article uses three Machine Learning algorithms, Random Forest, Gradient Boosting, and Support Vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In the framework of the IoMT, the paper [14] tackles the crucial cybersecurity problem. The authors aimed to create efficient techniques for the identification and cessation of cyberattacks in IoMT environments.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…In the framework of the IoMT, the paper [14] tackles the crucial cybersecurity problem. The authors aimed to create efficient techniques for the identification and cessation of cyberattacks in IoMT environments.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…When evaluating a network's performance, the routing protocol should be taken into account, as suggested by Jayalakshmi et al [20], who argued in favor of strengthening network security by using cryptography at every node. As proposed by Almomani [26], based on these suggestions, NIDSs can incorporate feature selection models to enhance their functionality. The development of this concept was motivated by the multitude of optimization strategies available, such as the particle swarm optimization (PSO), grey wolf optimization (GWO), firefly algorithm (FFA), and genetic algorithm (GA).…”
Section: Related Workmentioning
confidence: 99%
“…In order to spot cyberattacks, Tauqeer et al [26] employs a trifecta of Machine Learning algorithms: Random Forest, Gradient Boosting, and Support Vector Machine (SVM). The most effective models for detecting cyberattack are those trained with machine learning.…”
Section: Related Workmentioning
confidence: 99%
“…There have been multiple cyberattacks on the healthcare business, and millions of people's data have been released online. Upon analysis of different research [14,15] regarding cybersecurity in the healthcare sector, it is observed that those approaches only utilize a single technology. This results in a dilemma of whether to store the patient data securely or to analyze the data for tampering with the patient's health data.…”
Section: Motivationmentioning
confidence: 99%